2013
DOI: 10.1175/jamc-d-12-0149.1
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Silver Iodide Cloud-Seeding Parameterization in WRF. Part II: 3D Simulations of Actual Seeding Events and Sensitivity Tests

Abstract: Four cloud-seeding cases over southern Idaho during the 2010/11 winter season have been simulated by the Weather Research and Forecasting (WRF) model using the coupled silver iodide (Agi) cloud-seeding scheme that was described in Part I. The seeding effects of both ground-based and airborne seeding as well as the impacts of model physics, seeding rates, location, timing, and cloud properties on seeding effects have been investigated. The results were compared with those from Part I and showed the following: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…Two recent cloud seeding projects utilized snow chemistry data to inform statistical models or to parameterize weather model inputs: SNOWIE and the WWMPP [10][11][12]. Models are rapidly advancing the ability to predict when and where AgI are active [10], but considerable uncertainties remain in these models regarding how nucleation and subsequent transport and deposition are parameterized [12].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent cloud seeding projects utilized snow chemistry data to inform statistical models or to parameterize weather model inputs: SNOWIE and the WWMPP [10][11][12]. Models are rapidly advancing the ability to predict when and where AgI are active [10], but considerable uncertainties remain in these models regarding how nucleation and subsequent transport and deposition are parameterized [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the White Top Plan of the grain producing area in Missouri in Midwestern United States, rainfall decreased in areas near the downwind of cloud seeding line, but it increased farther downwind significantly (Decker et al, ). In addition, the dynamic effects caused by cloud seeding make the target area appear not only in the downwind direction of the operation site but may also affect the crosswind or even upwind direction (Wang et al, ; Xue, Hashimoto, et al, ; Xue, Tessendorf, et al, ).…”
Section: Statistical Test Schemesmentioning
confidence: 99%
“…It compares the actual value with the estimated natural value with the assumption of no catalysis to establish the corresponding evaluation indicators to analyze the effect of cloud seeding (Breed et al, ; Gabriel, ). Most previous studies selected precipitation to conduct analysis, and the results showed that the relative effects of artificial precipitation enhancement operation are about 5%–45% (e.g., Gabriel & Gagin, ; Gabriel, ; Gagin & Gabriel, ; Griffith & Yorty, ; Jia et al, ; Koloskov et al, ; Li et al, ; Morrison et al, ; Solak et al, ; Xue, Hashimoto, et al, ; Xue, Tessendorf, et al, ; Woodley et al, , ; Wu et al, ; Wurtele, ; Zeng et al, ; Zhai, ; Zhai et al, ). Despite important progress, many critical issues or challenges remain to be solved, such as natural fluctuation of spatial and temporal distribution of precipitation, lacking complete and systematic understanding of the processes of artificial catalysis and physical mechanism of cloud seeding, and limitation of the application of statistical methods.…”
Section: Introductionmentioning
confidence: 99%
“…The applications of AgI in photography, ice nucleation, cloud seeding, the superionic devices, and photocatalysis are well known . AgI thin films are also being investigated as resistive memories and optical waveguides .…”
Section: Introductionmentioning
confidence: 99%